Bullying Victimization Profiles of School-Aged Adolescents and Associations With Weight Statuses: A Latent Class Analysis. Issue 23 (December 2021) - Lee, Jungup; Hong, Jun Sung; Tan, Kevin; Pineros-Leano, Maria; Baek, Seung Ae
Bullying and childhood obesity are public health concerns in the United States. While obesity has been found to be associated with bullying victimization, it is less clear how it is differentially associated with biological sex and grade level across varying patterns of bullying victimization. Based on the subset of U.S. students in the Health Behavior in School-Aged Children study, patterns of co-occurring bullying victimization and sex and grade level differences in the association between the patterns of bullying victimization and weight status were examined among 9, 124 students in Grades 5 to 10. The latent class analysis revealed three patterns of bullying victimization: verbal-relational victimization (Class 1), all-type victimization (Class 2), and noninvolved pattern (Class 3). The results found that females had a higher likelihood of being in Class 1 than males. Moreover, fifth to sixth and seventh to eighth-graders were more likely than ninth to tenth graders to be in both Class 1 and Class 2. Obese males and overweight females were more likely to be in Class 1 and Class 2 than in Class 3. In addition, obesity and overweight status were positively associated with bullying victimization among fifth to sixth and seven to eighth-graders. However, no significant association was found between obesity and overweight status and bullying victimization among ninth to tenth graders. Findings from the study suggest that school-based strategies, especially sex- and age-specific programs, need to take into consideration the bullying involvement of students who are overweight or obese.